Trophic relationships between people and resources: fish consumption in an artisanal fishers neighborhood in Southern Brazil - Castro, Maísa Sousa; Martins, Ivan Machado; Hanazaki, Natalia (Ethnobiology and Conservation, 2016)
The study of dietary consumption is important to understanding the relationship between eating habits and natural resources, which may reflect adjustments and adaptations demanded by local environmental changes. This study aimed to understand the trophic relationships between the local families’ diets and the ichthyofauna present in an urban neighborhood of artisanal fishers in southern Brazil (Tijucas, Santa Catarina). Data were collected through semi-structured interviews in 88 households who reported the consumption of 62 types of fish, where the most consumed were the mullet (Mugil spp.) and croaker (Micropogonias furnieri). Fish is still an important source of animal protein for local families. Preferences and aversions observed can be explained by the relationship between environmental factors and cultural aspects that relate to the economic and social context of the community. In the last decade fish consumption was affected by local immigration and by contextual changes affecting local fisheries.